Confined transverse-electric graphene plasmons in negative refractive-index systems - Zhang, Xinyan (2023)
Transverse electric graphene plasmons are generally weakly confined in the direction perpendicular to the graphene plane. They are featured by a skin depth δ, namely the penetration depth of their evanescent fields into the surrounding environment, much larger than the wavelength λ in free space (e.g., δ > 10λ). The weak spatial confinement of transverse electric graphene plasmons is now the key drawback that limits their practical applications. Here we report the skin depth of TE graphene plasmons can be largely decreased down to the subwavelength scale (e.g., δ < λ/10) in negative refractive-index environments. The underlying mechanism originates from the different existence conditions for TE graphene plasmons in negative and positive refractive-index environments. To be specific, their existence in negative (positive) refractive-index environments requires Im(σs) > 0 (Im(σs) < 0) and lies in the frequency range of ħω/μc < 1.667 (ħω/μc > 1.667), where σs and μc are the surface conductivity and chemical potential of monolayer graphene, respectively.